(untitled) (International Journal of Engineering and Computer Science, 2016)
The IoT plays an important role in healthcare applications, from managing chronic diseases at one end of the spectrum to preventing disease at the other. The Internet of Things (IoT) has made it possible for devices around the world to acquire information and store it, in order to be able to use it at a later stage. However, this potential opportunity is often not exploited because of the excessively big interval between the data collection and the capability to process and analyze it. In this paper, an intense research has been carried out to explore the role of IoT healthcare delivery and also analyze the realistic opportunities of it. Finally high-end cloud computing technology based IoT framework is proposed to find the health care solutions in healthcare industry in reliable manner.